Stress, Physical Activity, Sedentary Behaviour and Resilience Resources: Tests of Cross-Sectional and Longitudinal Effects - Lines, Robin L.J. (Curtin University, 2019)
Stress can have a deleterious effect on physical activity and sedentary behaviour, though this effect does not hold for everyone. Resilience resources are an under studied potential moderator of this relationship. This supposition was examined using cross-sectional and longitudinal methods utilising self-report and physiological measures of key variables. Although resilience resources did not moderate these associations, they had a salubrious effect on people’s perceived stress, physical activity, and sedentary behaviour levels.